Theory and Description in African Linguistics - Clem, Emily; Jenks, Peter; Sande, Hannah (My University, 2019)
The papers in this volume were presented at the 47th Annual Conference on African Linguistics at UC Berkeley in 2016. The papers offer new descriptions of African languages and propose novel theoretical analyses of them. The contributions span topics in phonetics, phonology, syntax, semantics, and pragmatics and reflect the typological and genetic diversity of languages in Africa. Four papers in the volume examine Areal Features and Linguistic Reconstruction in Africa, and were presented at a special workshop on this topic held alongside the general session of ACAL.
Keywords: African Linguistics; Theory; phonology